Community Participation in Tourism Destination Development: Lesson from Kelor Tourism Village - Peni Arianita Wardani; Meiga Rahmanita; Muhamad Farhan; Rizqi Febrian Pramudita (Journal of Language, Communication, and Tourism, 2023)
Kelor Tourism Village is a tourism destination that is well-developed in Sleman Regency. This study aimed to analyze the forms of community participation in developing Kelor Tourism Village as a tourism destination. Qualitative descriptive method was used to describe the phenomena in the research object by using observation, interviews, and documentation to collect the data. This study showed the form of community participation in Kelor Tourism Village which consisted of two types: direct and indirect participation. The direct participation could be seen in the participation of the villagers, which included providers of tourist attractions, homestay providers, and the managers of Pokdarwis, in making decisions in every stage of the development of the tourist village. Meanwhile, the form of indirect participation carried out by the villagers was the participation in investing the operational costs of the tourism village. These participation forms have been solidly built since the beginning of their formation until now. The administrators’ enthusiasm in encouraging the community was a factor to grow their sense of ownership. Strong participation among the community also made Kelor Tourism Village economically independent and sustainable.